Asymptomatic Presentation in Arrhythmogenic Right Ventricular Cardiomyopathy: a Case Report. - Hirachan, Anish; Sharma, Ranjit; Neupane, Prabesh; Gautam, Milan; Ghimire, Ram Kumar (Nepalese Heart Journal, 2021)
Arrythmogenic right ventricular cardiomyopathy (ARVC) is an inherited cardiac condition leading to one of the common cause for sudden cardiac death in young individuals. It is characterized by fibrofatty replacement of the cardiac myocytes predominantly the right ventricle. As the presentation can be varied and very nonspecific, it often leads to delay in diagnosis and specific treatment. Here, we present a 30 year male who was asymptomatic and detected to have electrocardiograph (ECG) and echocardiographic abnormalities suggestive of ARVC. Further, a cardiac imaging with cardiac MRI confirmed the diagnosis of ARVC highlighting the importance of multimodality imaging.